2001
DOI: 10.1106/tq0x-nbbv-rpd6-vwhh
|View full text |Cite
|
Sign up to set email alerts
|

New Technology for Viscoelastic Foam

Abstract: The production and use of slow recovery “viscoelastic” polyurethane foams have increased rapidly over the past few years. Their unique performance characteristics, which include shape conformance, vibration and sound damping, and energy and shock absorption, make these the foams of choice for many diverse applications such as pillows, mattress toppers, automotive trim, sports and medical equipment, and ergonomic cushions and pads. These diverse applications require a wide range of foam grades with tailored per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The foam samples from the present investigation showed a rebound resilience value of 3%, whereas the value for the commercially available sample was 5%. The time taken by the foam to return to 95% of its original height after being compressed for one minute to 25% of its initial height was used to indicate the memory character of the specimens [11]. In this aspect also the foam developed in the present study was found to be better than its commercially available counterpart.…”
Section: Mechanical Propertiesmentioning
confidence: 72%
“…The foam samples from the present investigation showed a rebound resilience value of 3%, whereas the value for the commercially available sample was 5%. The time taken by the foam to return to 95% of its original height after being compressed for one minute to 25% of its initial height was used to indicate the memory character of the specimens [11]. In this aspect also the foam developed in the present study was found to be better than its commercially available counterpart.…”
Section: Mechanical Propertiesmentioning
confidence: 72%
“…The SEM images in Figure 8 show that the reference VE foam has mostly open cell structure, with cell windows completely open. Having an open cell structure with ruptured windows is a desirable property for VE foams, ensuring that the foam is fully compressible and dimensionally stable 45–52 . VE foams containing alpha‐1,3‐glucan polyol dispersion also have uniform cells with open cell structure.…”
Section: Resultsmentioning
confidence: 99%
“…Since the introduction of the line of VE products into the market, there have been numerous reports in scientific journals and conference proceedings on some of the features of VE‐related foam materials and their fundamental properties; these have all focused on the use of polyols derived largely from petroleum feedstocks 17, 30, 32–43. (Glycerin, which could be from natural or synthetic origins, is used in the manufacture of some VE polyols.…”
Section: Introductionmentioning
confidence: 99%
“…Two us also previously addressed many of the formulation variables that influence the mechanical behavior of largely petroleum‐based unimodal‐ T g VE foams and their temperature dependence 34, 36. Kageoka et al,33 in addition, provided some more detailed studies on the loading rate dependence in conjunction with the temperature variability of VE foams in view of the strong importance of these coupled variables to the actual in‐use behavior of such products.…”
Section: Introductionmentioning
confidence: 99%